2012
DOI: 10.1021/jm300390f
|View full text |Cite
|
Sign up to set email alerts
|

6-(Methylamino)hexane-1,2,3,4,5-pentanol 4-(((1S,2S)-1-Hydroxy-2,3-dihydro-1H,1′H-[2,2-biinden]-2-yl)methyl)benzoate (PH46A): A Novel Small Molecule With Efficacy In Murine Models Of Colitis

Abstract: The indane skeleton is found naturally and in several therapeutic molecules in medicinal chemistry. During our work on the anti-inflammatory activity of naturally occurring and synthetic indanes, we have synthesized a novel indane scaffold that has been optimized for both anti-inflammatory activity and bioavailability. We have evaluated our lead molecule, PH46A, in in vivo models of inflammatory bowel disease (IBD), an area of considerable unmet clinical need; current therapies are often unable to control the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…The detailed NMR spectra and chromatograms are provided in Supplementary Figures S22-S28. 1 H and 13 C NMR data of PH46 were in agreement with the data we previously reported (Figures 9 and 10) [17]. The 1 H NMR spectrum of PH132 ( Figure 11) shared similar spectral pattern as that of PH46.…”
Section: Recombinant Enzymes and Microsomes Screeningsupporting
confidence: 90%
See 1 more Smart Citation
“…The detailed NMR spectra and chromatograms are provided in Supplementary Figures S22-S28. 1 H and 13 C NMR data of PH46 were in agreement with the data we previously reported (Figures 9 and 10) [17]. The 1 H NMR spectrum of PH132 ( Figure 11) shared similar spectral pattern as that of PH46.…”
Section: Recombinant Enzymes and Microsomes Screeningsupporting
confidence: 90%
“…In continuation of our work, we more recently designed and synthesized a series of dimeric indane compounds, with two contiguous stereogenic centres, one of which is a quaternary centre. Some of these compounds possess potent anti-inflammatory activity, in particular, a lead chiral molecule PH46A with S,S configurations [14][15][16][17][18], has been identified by our group and was subject to a range of preclinical studies prior to entering a Phase I clinical trial [19]. ADME (Absorption, distribution, metabolism, and excretion) is one of the major elements involved in the drug discovery and development process.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the glutamine salt of the S,S ‐enantiomer of the carboxylic acid derivative of PH5, PH46A has good efficacy in both DSS‐colitis and the IL10 −/− model of spontaneous colitis, models with very different aetiologies . Furthermore, PH46A does not inhibit IL2 release from Jurkat cells (see Fig.…”
Section: Discussionmentioning
confidence: 95%
“…For background to the indanone pharmacophore, its use as an organic intermediate and its biological activity, see: Buckle et al (1973); Sheridan et al (1990Sheridan et al ( , 1999aSheridan et al ( ,b, 2008Sheridan et al ( , 2009a; Vacca et al (1994); Schumann et al (2001); Herzog et al (2002); Frankish et al (2004); Frankish & Sheridan (2012); Dinges et al (2006); Kou et al (2012); Ito et al (2004); Jaki et al (1999); Chanda et al (2012); Chen et al (2008); Rukachaisirikul et al (2013); Farrell et al (1996); Borbone et al (2011); Fu & Wang (2008). For bond lengths and angles in related compounds, see: Ali et al (2010aAli et al ( ,b, 2011…”
Section: Related Literaturementioning
confidence: 99%